2014
DOI: 10.5090/kjtcs.2014.47.6.517
|View full text |Cite
|
Sign up to set email alerts
|

The Factors Affecting Recurrence of Symptoms after Infrainguinal Arterial Endovascular Angioplasty

Abstract: BackgroundThis study reports the result of endovascular treatment for arterial occlusive disease limited to femoropopliteal lesions, focusing on the recurrence of symptoms instead of patency.MethodsThis was a retrospective, single-center study. From April 2007 to November 2011, 48 limbs in 38 patients underwent endovascular stenting or balloon angioplasty to treat femoropopliteal arterial occlusive disease. The factors affecting the recurrence of symptoms were analyzed.ResultsThe mean age of the patients was 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…However, many patients are poor candidates for these interventions due to their comorbidities such as diabetes despite the availability of treatment options [ 7 ]. Moreover, 20% of treated patients develop recurrent symptoms that cannot further undergo vascular intervention [ 8 , 9 ]. Thus, the induction of endogenous revascularization has been attempted to establish an alternative strategy of revascularization that ensures efficient re-establishment of blood flow to ischemic tissues and improve PAD patients’ clinical outcomes.…”
mentioning
confidence: 99%
“…However, many patients are poor candidates for these interventions due to their comorbidities such as diabetes despite the availability of treatment options [ 7 ]. Moreover, 20% of treated patients develop recurrent symptoms that cannot further undergo vascular intervention [ 8 , 9 ]. Thus, the induction of endogenous revascularization has been attempted to establish an alternative strategy of revascularization that ensures efficient re-establishment of blood flow to ischemic tissues and improve PAD patients’ clinical outcomes.…”
mentioning
confidence: 99%
“…In the study by Bae et al . [ 20 ], the presence of a dorsal arch (HR = 0.66, p = 0.047) and dyslipidemia (HR = 5.81, p = = 0.031) were significant factors affecting the recurrence of symptoms after endovascular treatment of occlusive femoro-popliteal lesions. Moreover, other studies have shown the importance of BTK outflow quality for the patency of stents implanted into femoro- popliteal vascular segments [ 1 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Visto que a DAOP dos MMII é um problema de saúde pública crescente, com altos custos para o paciente e para o sistema de saúde, é necessário pesquisar exames menos invasivos e de baixo custo que possam ajudar na decisão terapêutica mais adequada para seus portadores. Sugerindo inclusive, qual artéria deveria ser revascularizada [6][7][8][9][10][11][12][13][14][15][16][17][18] .…”
Section: Introductionunclassified